New Approaches, More Transdisciplinarity. The Impact of Globalization in the Historiography of 21st. Century - Rivera Aravena, Carla (Revista de Historia Social y de las Mentalidades, 2024)
The historiography of the 21st century embraced new themes, approaches, and methodologies with the advance of globalisation and technology, which came to signify the past. This issue comprises different proposals for historical analysis, but they all have one element in common: interdisciplinarity.
Keywords: His; Historiography